Improving Elementary School Teacher Competency Through Portfolio Assessment in Low Grade - Hamid Darmadi (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2020)
The purpose of this study was to obtain objective information and clarity regarding Elementary School Teacher Competitions through Low grade Portfolio Assessment. The results of this study indicated that the development of thematic learning models through the assessment of low-grade portfolio by Bengkayang District Elementary school teachers is in a "sufficient" position. The planning of learning model by elementary school teachers in urban areas had an actual score of 495 and an ideal maximum score of 840 or 58.92% with the category "sufficient." In the suburbs, it had an actual score of 334 and an ideal maximum score of 840 or 39.76% with the "enough" category. While in areas outside the urban area have an actual score of 335 and an ideal maximum score of 840 or 39.88% with the category also "sufficient." In each assessment effect, model planning effect in the Urban area obtained an actual total score of 96 ideal maximum score of 144, = 66.67%; At the Suburbs the actual score was 48 ideal scores 144 = 33.44%; while for the Outer Urban area obtained an actual score of 47 ideal scores 144 = 32.64%. The aspect of the preparatory stage for the implementation of the thematic learning model of low-grade portfolio assessment by elementary school teachers in the urban area obtained an actual score of 80 from an ideal maximum score of 120, reaching 66.67%; Suburbs obtained an actual score of 53 ideal scores 120 = 44.16%; Whereas in the out-of-urban effect urban area, the actual score was 52 ideal scores 120 = 43.33%. Implementation Stage Thematic learning model in the assessment of low-grade portfolio in the urban area obtained an actual score of 201 ideal maximum score of 360, = 55.83%; In the suburbs the actual score: 161 ideal scores 360 = 44.72%; while Out of urban the actual score is 162, the ideal score is 360 = 45.00%. The aspect of How to assess thematic learning models in the assessment of low-grade portfolio in the Urban area obtained the total score of 62 ideal maximum scores of 96, = 64.58%; Suburbs actual score 29 ideal score 96 = 30.21%; While out of urban the actual score of 31 was an ideal score of 96 = 32.29%. The aspect of the implication of thematic learning in the assessment of low-grade portfolio in the urban area obtained the number of actual scores of 57 ideal maximum scores of 120, = 47.50%; Suburbs actual score 43 ideal scores 120 = 35.83%; Out of urban the actual score of 43 was an ideal score of 120 = 35.83% of what it should be. For this reason, it was suggested thematic learning model planning for portfolio assessment should continued to be maintained by increasing the ability to compile annual programs, compile semester programs, compile syllabi, compile lesson plans, compile mapping and learning theme networks. The thematic learning model of portfolio assessment was not rigid but flexible, adapts existing situations, and conditions were active, creative, effective, and pleases learners referring to the concept of independent learning implementation of thematic learning of portfolio assessment by conducting initial activities, core activities, and closing / ending activities. Assessment of the thematic learning model portfolio assessment referred to indicators that have been determined by the education authority. Implications of implementing thematic learning model portfolio assessment was done by giving individual and group assignments by not burdening students, and utilizing and optimizing available learning media.